Potassium Channels as a Target for Cancer Therapy: Current Perspectives - Vilos-Ortiz, C (Dove Medical Press Ltd, 2022)
Potassium (K+) channels are highly regulated membrane proteins that control the potassium ion flux and respond to different cellular stimuli. These ion channels are grouped into three major families, Kv (voltage-gated K+ channel), Kir (inwardly rectifying K+ channel) and K2P (two-pore K+ channels), according to the structure, to mediate the K+ currents. In cancer, alterations in K+ channel function can promote the acquisition of the so-called hallmarks of cancer – cell proliferation, resistance to apoptosis, metabolic changes, angiogenesis, and migratory capabilities – emerging as targets for the development of new therapeutic drugs. In this review, we focus our attention on the different K+ channels associated with the most relevant and prevalent cancer types. We summarize our knowledge about the potassium channels structure and function, their cancer dysregulated expression and discuss the K+ channels modulator and the strategies for designing new drugs. © 2022 Zúñiga et al.